Depressive symptoms and quality of life among women experiencing infertility: The moderating effect of perceived social support - Minjeong Jo; Hyewon Shin; Angela Kabbe; Shin-Jeong Kim (Heliyon)
Background: Infertility constitutes a leading reproductive health problem with profound psychosocial outcomes, including elevated depressive symptoms that compromise quality of life (QoL). While the literature has suggested social support as a protective psychological mechanism, its role in depressive symptoms and QoL among women with infertility remains underexplored. This study aimed to examine the moderating effect of perceived social support on the relationship between depressive symptoms and QoL among South Korean women experiencing infertility. Methods: Utilizing a cross-sectional design, this study analyzed a secondary dataset comprising 186 South Korean women with infertility. Participants were asked to complete the online survey which included the following scales: The Korean adaptation of the Patient Health Questionnaire-9 (PHQ-9), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Fertility Quality of Life (FertiQoL) tool. Moderation analysis was conducted using Hayes' PROCESS Macro 4.1 Model 1. Statistically significant effects were identified if the confidence intervals did not include zero. Depression acted as the predictor, social support as the moderator, and QoL as the dependent variable. Results: Depressive symptoms exhibited a moderate negative relationship with fertility QoL (r = −.41, p < .001). When stratified by PHQ-9 severity, correlations between depressive symptoms, social support, and fertility QoL were only significant for the group with mild or no depressive symptoms. In this group, depressive symptoms negatively predicted fertility QoL (ß = −.92, p < .05), and a significant interaction effect between depressive symptom severity and social support on fertility QoL was observed (ß = −1.24, p < .05). Conclusion: Perceived social support has a moderating effect on the relationship between depressive symptoms and fertility QoL only for women with mild or no depressive symptoms. Consequently, nursing interventions for South Korean women with infertility should focus on emotional and social support, which include enhancing individual coping skills and facilitating community-based support networks. These can be implemented through specialized educational initiatives and expert-moderated online forums, aiming to enhance the emotional well-being of women experiencing infertility.